The newly industrializing countries of Asia - Tan, Gerald (Times Academic Press, 1995)
The failure of the neo-Marxist dependency perspectives to accommodate and come to terms with the possibilities of peripheral capitalist development in the four Newly Industrializing Countries (NICs) of East and Southeast Asia should not then result in the embracing of the stages approaches espoused either by modernization theory or by Warren. Rather, consideration should be given to approaches which emphasize, within the backdrop of the changing internationalization of the self-expansion of capital, the historical specificities of capital accumulation, class struggle and the role of the state in the process of social reproduction.